Service Relation and Organizational Context: A Qualitative Research at Shopping Centers - Cruz, Sofia Alexandra (Qualitative Sociology Review, 2015)
Service work has undergone changes related to their managerial practices, which bring new professional and organizational realities to employees. The purpose of this article is to explore the opportunities of a qualitative research strategy combining both semi-structured interviews and participant observations to consider work organization and analyze the existing modes of service work of different types of shops and restaurants within shopping centers. This analysis considers the existence of a complex service relation that incorporates relational and material dimensions.